Analisis Pengaruh Kualitas Pelayanan dan Nilai yang dirasakan Terhadap Kepuasan Konsumen dan Intensitas Pembelian - Ferdinandus, Leonora; Gomies, Stevanus Johan (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2021)
This research aims to analyze the impact of service quality and value in consumer satisfaction and feel the intensity of purchases on PT.Mulia Travel in Ambon, the instrument used was a questionnaire distributed to consumers PT. Travel noble by random sampling on the 300 respondents who met on the field during the period of this study. Data analysis methods used is to use the technique (Confirmatory Factor Analysis / CFA) to validate the questions on the questionnaire. The data collected were analyzed using multiple regression analysis, F test, t test and determination. The results showed that service quality variables are positive and significant effect on customer satisfaction, as well as the variable value in feeling positive and significant effect on customer satisfaction. Then the results of the study also showed that service quality variables are positive and significant effect on the intensity of consumer purchases, as well as the variable value in feeling positive and significant effect on the intensity of consumer purchases. So is the consumer satisfaction is positively and significantly affect the intensity of consumer purchases. Thus concluded the entire hypothesis is accepted. Keywords ; Quality of Service, Value in Feeling, Consumer Satisfaction, Intensity of Purchases